The Relationship Between Glucosamine Supplementation and Increased Intraocular Pressure in Patients With Open Angle Glaucoma (at Dr. Wahidin Soediro Husodo Hospital) - Rini Kusumawardhany (Universitas Muhammadiyah Surabaya, 2017)
Introduction and Objective Researchers postulate that excessive deposits of GAG in the trabecular meshwork restrict outflow. Another theory suggests that increased release of GAG into the aqueous causes an osmotic effect, drawing more water into the anterior chamber, thus causing swelling, a decrease in pore size, and eventually increased resistance to outflow.Either of these proposed mechanisms could lead to an increased thickness of the pore lining and/or decreased outflow, resulting in increased intraocular pressure (IOP). Methods A total of 13 patients (26 eyes) 6 men, 7 women, with average age 62 years were included in this experimental study. IOP was measured before, on 7th day after they began glucosamine supplementation and after discontinuation. Patients had been selected who established the diagnosis of open-angle glaucoma, willingness to using glucosamine, IOP measurements at least 3 times within 2 years, and no associated changes in glaucoma medications or eye surgery.Result Based on the parametric repeat measure general linear model test, the IOP decreased significantly from during glucosamine supplementation to discontinuation of glucosamine.(P= 0,013, or P< 0,05). The IOP was increased during glucosamine supplementation compared with before glucosamine supplementation, but the difference statistically not significant. (P= 0,527).The IOP decreased after discontinuation compared with before supplementation, but the difference also statistically not significant. (P=1). There was no significant difference between the left and right eyes in each patient.